Compartimentação aquática do reservatório Rodolfo Costa e Silva-RS, a partir de variáveis limnológicas e imagens orbitais - Wachholz, Flávio (2007)
A reservoir presents different environmental traits as a function of the flooded area, water circulation pattern, residence time and nutrients entrance. This situation define the aquatic compartments. The objective was use limnological parameter dynamic and spectral data to identify aquatic compartments in the Rodolfo Costa e Silva reservoir, located on central region of the State of Rio Grande do Sul, on southern region of Brazil. The methodology was based on the measure of water transparence with Secchi disc, Total of Suspended Solids (TSS) and chlorophyll a, b and c. These data were monthly collected in 21 sampling points, distributed over the reservoir during hydrologic year (Oct. 2005 to Sept. 2006). However, chlorophyll samples were collected only two times in autumn season. Satellites images from China-Brazil Earth Resources Satellite 2 (CBERS 2 CCD) and Landsat 5 (TM) were used to make a comparison with limnological and field spectral data. The spatial distribution of limnological parameters was done after data interpolation (weighted average) and its analyses allowed the discrimination of aquatic compartments. During the hydrologic year the transparence changed between 100 and 315 cm and could be divided in two periods: a period with low transparences, from August to November (marked by land tillage for summer crop) and; period with high transparence, from December to June. Based on this variable, the reservoir presented three compartments: a) upstream, with lower transparence; b) downstream, with higher transparence; c) central region, even with high transparence. The TSS ranged from 0.17 to 14.16 mg/L in the hydrologic year. Its behavior was inversely to the water transparence but presented the same three compartments than transparence. The chlorophyll concentration varied from 0.63 to 24.19 μg/L and defined two compartments: upstream and downstream. A larger input of nutrients in upstream let the development of phytoplankton (chlorophylls). Results from CCD and TM images were better when TSS concentration was greater and transparence smaller, associated to the highest data variance. Concentrations of TSS up to 4 mg/L periods with low transparence allowed identify aquatic compartments with blue band (centered on 450 nm) and the red band (centered on 661 nm). The chlorophylls a and c showed absorption bands on the field spectrum of reflectance, making possible establish correlations with limnological parameters (TSS and transparence). Finally, the aquatic compartments that were found out are specially related to the entrance of organic and inorganic matter from terrestrial environment. TSS and chlorophyll decreases into downstream.